The Role of Integrated Schools in Improving Islamic Education in Muslim Minority Areas of Cambodia - Wien Anisa Yahyani; Rido Kurnianto; Ayok Ariyanto (Al-Hayat Al-Istiqomah Foundation, 2020)
This study aims to find out how to improve Islamic religious education in the Krouch Chmar area, Cambodia where this area is an Islamic village in the middle of Cambodia, which is a majority Buddhist community, then the Musa Asih Integrated School (SEPAMA) is present which has a role in helping increase in Islamic education. This research uses qualitative methods, data collection using observation, interviews and documentation, qualitative data analysis is carried out continuously to completion. The findings of this researcher are that Islamic religious education in the Krouch Chmar area began to develop with the existence of an integrated school system where this school has a combination of curriculum, namely the national curriculum and the Islamic religious education curriculum, through this school finally Islamic religious education begins to increase because children and the community can easily learn Islamic religious education, this is supported by programs owned by SEPAMA, so that from this school it provides a role in improving Islamic religious education in Islamic minority areas in Cambodia, starting from a pedagogical role, a moral-spiritual role and a socio- culture which ultimately improves Islamic religious education in the area.